GRPR Drives Metastasis via CRABP2 and FNDC4 Pathways in Lung Adenocarcinoma - Dong-Gun Kim; Eun-Young Choi; Hye-Mi Ahn; Youn-Jae Kim (Cells)
Metastasis is a leading cause of lung adenocarcinoma (LUAD)-related mortality and presents significant challenges for treatment. The gastrin-releasing peptide receptor (GRPR), a member of the G protein-coupled receptor (GPCR) family, has an unclear role in LUAD progression. This study aimed to investigate the function and underlying mechanisms of GRPR in LUAD metastasis. Our findings revealed that GRPR levels were significantly elevated in tumor tissues, and higher GRPR expression was associated with worse overall survival outcomes. Functional assays demonstrated that GRPR overexpression enhanced LUAD cell invasion, while GRPR knockdown inhibited invasion both in vitro and in vivo. RNA sequencing and gene set enrichment analysis (GSEA) identified an enrichment of metastasis-promoting genes in GRPR-overexpressing cells, with CRABP2 and FNDC4 emerging as key targets. Clinical analyses further confirmed a positive correlation between GRPR expression and the levels of CRABP2 and FNDC4 in LUAD patients. These results suggest that GRPR could serve as both a prognostic marker and a therapeutic target to inhibit metastasis in LUAD.